(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
In the present paper additional occurrence of 100 species in 75 genera under 40 angiosperm families in the Runctia Sal Forest of Sherpur district is reported. Of these, 71 species in 56 genera are from Magnoliopsida (Dicots) and 29 species in 19 genera are from Liliopsida (Monocots). These species exhibit in diverse life forms in the area, viz., 54 species are herbs, 21 species shrubs, 12 species climbers and 13 trees. Holigarna longifolia is threatened in the Sal forest area which needs to give conservation priorities. An enumeration of the species recorded is presented with important synonyms, Bengali names, habit, habitat and representative specimens. Keywords: Angiosperms; Runctia sal forest; Addition. DOI: 10.3329/bjpt.v17i2.6696 Bangladesh J. Plant Taxon. 17(2): 167-181, 2010 (December)